(untitled) (European Journal of Pure and Applied Mathematics, 2010)
It is well known that in economics and finance, the data usually have â€œfat tailâ€ and in this case the Normal distribution is not a good model to use. The skew normal distributions recently draw considerable attention as an alternative model. Unfortunately, the distribution of the sum of log-skew normal random variables does not have a closed form. In this work, we discuss the use of lower convex order of random variables to approximate this distribution. Further, two application of this approximate distribution are given : first to describe the final wealth of a series of payments, and second to describe the present value of a series of payments.